The Impact of Climate Change on Global Economic Stability: Developing Economic Policies to Manage Climate Risks - Angwaomaodoko, Ejuchegahi Anthony (Issues in Economics and Business, 2024)
The paper explores the impact of climate change on global economic stability while also placing consideration on the role of economic policy towards the management of climate change risk. Climate change represents one of the pressing environmental challenges of the 21st century with profound repercussion on the economic stability while also affecting several sectors such as agriculture, energy, tourism and health. The increased rate of change in the climatic condition has led to a wide spread of severe weather conditions such as hurricanes, flooding, drought, tsunamis, wild fire etc. This has necessitated the need for a robust economic policy that would aid in the mitigation effort against the release of greenhouse gases into the atmosphere, as well as providing adaptation against the harmful impact of climate change. The role of the agreement of 2015 Paris frame work was examined as it provides an important foundation for global cooperation in the fight against climate change. It is expected that proper integration of financial institution and the private sector would provide the necessary funding and technical support that would aid in the implementation of green technology as well as promote sustainable development.